Hubungan Kadar Debu Total, Karakteristik Pekerja, Dan Perilaku Individu Terhadap Keluhan Subjektif Gangguan Pernapasan Pada Tenaga Kerja Bongkar Muat (TKBM) Di Pelabuhan Marunda, Jakarta Utara Tahun 2023 - Budi Pramono; Atang Saputra; Syarifuddin; Syathiroh (BULLET : Jurnal Multidisiplin Ilmu, 2023)
Air pollution is an event of mixing of harmful elements, both chemical, physical and biological elements in one atmosphere which can have a negative impact on living things and their environment. One of the substances of air pollution is dust. Dust will become dangerous if inhaled into the human respiratory tract and cause respiratory problems. This study entitled "The Relationship between Total Dust Content, Worker Characteristics, and Individual Behavior Against Subjective Complaints of Respiratory Disorders at (unloading workers) in Marunda Port, North Jakarta in 2023" uses an analytic survey study method with a cross sectional research design. Data collection was carried out by measuring dust levels using an HVS (High Volume Sampler) measuring instrument and interviews using a questionnaire with a total of 24 respondents from 160 the worker. Data were analyzed univariately and bivariately using the Chi-square statistical test. The scope of this study included total dust content, worker characteristics (age, education, years of service, length of exposure, and nutritional status) and individual behavior (use of PPE, smoking habits, and exercise habits) on subjective complaints of respiratory disorders. The conclusions obtained after the authors conducted the research that there was a significant relationship between age (p-value = 0,023; OR = 0,069), and years of service (p-value = 0,009; OR = 0,053), to subjective complaints respiratory problems at (Loading and Unloading Workers) in Marunda Port, North Jakarta. While there is no relationship between education, length of exposure, nutritional status, use of personal protective equipment, smoking habits, and exercise habits on subjective complaints of respiratory problems at (Unloading Workforce) in Marunda Port, North Jakarta.